Analysis of Customer Value and Customer Experience on Customer Satisfaction and Loyalty - Bogi Akhmad Suendar; Endi Sarwoko; Andreas Jodhinata (International Journal of Economics and Management Research, 2025)
The competitive rivalry in the ship classification service business poses a unique challenge for PT. Indonesian Classification Bureau (Persero) to enhance the company's competitive advantage, with maritime safety and service quality being prioritized to achieve customer satisfaction and loyalty. The objectives of this research are (1) To determine the partial effect of customer value and customer experience on customer satisfaction; (2) To determine the partial effect of customer value and customer experience on customer loyalty; (3) To determine the effect of customer satisfaction on customer loyalty; (4) To determine the effect of customer value on customer loyalty through the mediation of customer satisfaction; (5) To determine the effect of customer experience on customer loyalty through the mediation of customer satisfaction. The approach used in this research is quantitative. A sample of 90 people was selected using the Random Sampling technique. The data collection method used a questionnaire. The data analysis technique used SEM with PLS. Based on the results of this study, it was found that the customer experience variable significantly affects both the customer satisfaction variable and the customer loyalty variable. Furthermore, the customer value variable affects the customer satisfaction variable but does not significantly affect the customer loyalty variable. The customer satisfaction variable affects customer loyalty. For indirect variables, both the customer experience variable and the customer value variable affect customer loyalty, mediated by customer satisfaction. This study has limitations, namely that some respondents did not fully understand the statements in the questionnaire when it was administered. Suggestions for future researchers include creating a questionnaire with appropriate sentences and language that are easier for respondents to understand, and adding more variables.